198k views
2 votes
Find an explicit formula for f(n). ​

Find an explicit formula for f(n). ​-example-1

1 Answer

2 votes

Answer:

f(n) = 2n - 2

Explanation:

Given the recursive formula

f(n) = f(n - 1) + 2 with f(1) = 0, then

f(2) = f(1) + 2 = 0 + 2 = 2

f(3) = f(2) + 2 = 2 + 2 = 4

f(4) = f(3) + 2 = 4 + 2 = 6

The terms of the sequence are 0, 2, 4, 6, ....

These are the first 4 terms of an arithmetic sequence with explicit formula

f(n) = a₁ + (n - 1)d

where a₁ is the first term and d the common difference

Here d = 2 - 0 = 4 - 2 = 6 - 4 = 2 and a₁ = 0, thus

f(n) = 0 + 2(n - 1), that is

f(n) = 2n - 2 ← explicit formula

User Aldan Creo
by
4.7k points